The World Trade Center attack: mental health needs and treatment implications - Herman, Daniel B. (Int Psychiatry, 2003)
On 11 September 2001, the United States suffered the worst terrorist attacks in its history. In New York City, approximately 3000 persons were killed at the World Trade Center, while many thousands fled for their lives. Millions of other city residents observed the burning towers and breathed the acrid smoke that blanketed the city. Compounding the massive physical destruction and loss of life, the psychological impact of these terrifying events on the populace was profound – there were significant increases in mental distress and symptoms of disorder.